1993
DOI: 10.1016/s0886-3350(13)80341-0
|View full text |Cite
|
Sign up to set email alerts
|

Corneal endothelial and intraocular pressure changes after phacoemulsification with Amvisc Plus and Viscoat

Abstract: A prospective, randomized, observer-marked study was conducted to compare corneal endothelial and intraocular pressure (IOP) changes after cataract surgery with the viscoelastic agents Amvisc Plus and Viscoat. Forty-nine patients (50 eyes) who had uncomplicated phacoemulsification and implantation of a posterior chamber intraocular lens were randomly assigned to either Amvisc Plus (25 eyes) or Viscoat (25 eyes) groups. Surgical technique was rigidly standardized in all cases. No significant difference in endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Its effect on postoperative IOP after phacoemulsification is well documented, 7,8 and it has been shown to induce greater increases in IOP than other OVDs. 7,[9][10][11] Various ocular hypotensive agents 12-16 and intracameral cholinergic agents 17,18 have been used to…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its effect on postoperative IOP after phacoemulsification is well documented, 7,8 and it has been shown to induce greater increases in IOP than other OVDs. 7,[9][10][11] Various ocular hypotensive agents 12-16 and intracameral cholinergic agents 17,18 have been used to…”
Section: Resultsmentioning
confidence: 99%
“…These devices can cause increases in IOP; however, the mechanisms responsible for these increases have yet to be elucidated. 6,7,[9][10][11] A major reason for postoperative increases in the IOP appears to be the amount of OVD remaining at the end of surgery. Ophthalmic viscosurgical devices can contribute to obstruction of the aqueous outflow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It has been demonstrated that increased phacoemulsification ultrasonic energy expenditure, defined by machine-measured phacoemulsification time and mean percentage of maximum power, is associated with increased corneal ECD loss. 14,17,[22][23][24][25] Endothelial cell density loss is reported to be 4% to 12% with divide-and-conquer techniques 4,7,16,17,26,27 and lower with stop-and-chop methods. 4 Regardless of technique, the location of the phacoemulsification process is important.…”
Section: Discussionmentioning
confidence: 99%
“…37 It has been demonstrated that increased phacoemulsification energy expenditure is associated with increased corneal ECD loss. 11,28,31,[38][39][40] Because of this, techniques and technology have evolved together with the intent to use less ultrasonic energy during phacoemulsification. Ultrasonic energy reductions have been achieved in 4 ways: (1) tip design [17][18][19]21 (Kelman phacoemulsification tip, personal 42 and NeoSoniX-generated tip rotations (Alcon Legacy 20000, Alcon Infinity); and (4) pulsed water jet technology (Aqualase, Alcon Infinity).…”
Section: Discussionmentioning
confidence: 99%